Persepsi Pelaku Usaha Mikro Kecil Menengah terhadap Kualitas Pelayanan Publik di Dinas Koperasi Kota Medan - Harahap, Adelia Rahmi; Siregar, Nina Siti Salmaniah; Kadir, Abdul (Universitas Medan Area, 2020)
This research was conducted in the field of UKM Empowerment of the Medan City Cooperative UKM Office, with the aim to determine the perceptions of Micro Business Actors on the quality of service in the field of UKM Empowerment of the Medan City Cooperative Office, to find out the factors that influence the quality of public services in the Field of UKM Empowerment of the Cooperative Office Medan City UKM. The research method used is a descriptive qualitative research method, with data collection techniques of observation, interviews and documentation. From the results of research by interviewing a number of SMEs, it is known that the perception of Micro Business Actors about the services of the Field of UKM Empowerment of the City of Medan SME Cooperative Office as a whole is satisfying. The theory used is a theory according to Zeithhaml, Pasuraman and Berry about the dimensions of service quality. The factors that affect service quality using indicators include: requirements, service time, costs / tariffs, implementing competencies and implementing behavior contained in the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 16 of 2014 and adjusted based on the theories of Zeithhaml, Pasuraman and Berry. Regarding facilities and infrastructure, the Medan City Cooperative Office has not yet created an information board that contains information on technical or administrative requirements, so Business Actors can find out.